Analysis of the Performance of The Four-Blade Darrieus Wind Turbine at the Jamik Bukit Asam Mosque Complex Tanjung Enim South Sumatra: Analysis of the Performance of The Four-Blade Darrieus Wind Turbine at the Jamik Bukit Asam Mosque Complex Tanjung Enim South Sumatra - Mustafa Kamal; Fatahul Arifin; Rusdianasari (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
Several types of renewable energy have been developed, such as solar energy, biomass, hydro energy, geothermal, and wind energy. Wind energy is an up-and-coming alternative and renewable energy. Wind energy is more environmentally friendly than available energy sources and has more accessible operational and maintenance costs. Indonesia has a relatively small natural wind energy potential because the wind speed in Indonesia is on average 3-6 m/s due to its location. Geographically, it is located in the equatorial area, especially the Muara Enim area, South Sumatra. This study aims to design a prototype the four-blade darrieus type vertical axis wind turbine (VAWT) needed for the utilization of wind energy which is used for Coffee Shop electricity needs at the Jamik Bukit Asam Tanjung Enim Mosque complex, South Sumatra, with the conclusion that the wind turbine, wind turbine rotation, the magnitude of the output voltage and The current generated significantly affects the wind speed in the area.